DEVELOPMENT OF PROFESSIONAL COMPETENCE OF TEACHER OF PRESCHOOL EDUCATION ORGANIZATIONS - D.B. Kasimova (Лучшие интеллектуальные исследования, 2023)
Abstract: Further improvement of the system of preschool education in our country, strengthening the material and technical base, expanding the network of preschool educational institutions, providing qualified teaching staff, a radical increase in the level of preparation of children for schooling, ways of education and upbringing, the use of modern educational programs in this process and technologies.